Indonesia's SME Tax Regulations: How We Can Improve Them? - Pratama, Arie (Universitas Pendidikan Indonesia, 2021)
This research aims to analyze whether there is an opportunity to improve the SME's tax regulations by examining six critical factors in the SME tax collection model. The research method applied for this research is a qualitative research model with an exploratory-descriptive approach. Data was collected using literature review and interviews with SME taxpayers residing in Bandung, West Java, Indonesia, and tax officers specializing in the SME tax model. Data were analyzed using content analysis. The research showed a significant gap in taxpayer's condition from 6 critical factors in the SME tax model. Research shows that taxpayer still has no or little knowledge of tax laws and tax procedure and administration itself, so the effort of tax office should be paced up, so SME taxpayer will understand tax laws and tax procedure and administration better.